Calcium-silicate mesoporous nanoparticles loaded with chlorhexidine for both anti- Enterococcus faecalis and mineralization properties - Wei Fan; Yanyun Li; Qing Sun; Tengjiao Ma; Bing Fan (Journal of Nanobiotechnology, 2016)
Abstract Background In infected periapical tissues, Enterococcus faecalis is one of the most common dominant bacteria. Chlorhexidine has been proved to show strong antibacterial ability against E. faecalis but is ineffective in promoting mineralization for tissues around root apex. Mesoporous calcium-silicate nanoparticles are newly synthesized biomaterials with excellent ability to promote mineralization and carry-release bioactive molecules in a controlled manner. In this study, mesoporous calcium-silicate nanoparticles were functionalized with chlorhexidine and their releasing profile, antibacterial ability, effect on cell proliferation and in vitro mineralization property were evaluated. Results The chlorhexidine was successfully incorporated into mesoporous calcium-silicate nanoparticles by a mixing-coupling method. The new material could release chlorhexidine as well as Ca2+ and SiO3 2− in a sustained manner with an alkaline pH value under different conditions. The antimicrobial ability against planktonic E. faecalis was dramatically improved after chlorhexidine incorporation. The nanoparticles with chlorhexidine showed no negative effect on cell proliferation with low concentrations. On dentin slices, the new synthesized material demonstrated a similar inhibitory effect on E. faecalis as the chlorhexidine. After being immersed in SBF for 9 days, numerous apatite crystals could be observed on surfaces of the material tablets. Conclusions Mesoporous calcium-silicate nanoparticles loaded with chlorhexidine exhibited release of ions and chlorhexidine, low cytotoxicity, excellent antibacterial ability and in vitro mineralization. This material could be developed into a new effective intra-canal medication in dentistry or a new bone defect filling material for infected bone defects.